Giulio Cesare [opera in three acts] - Händel, Georg Friedrich 1685-1759 (Opus Arte, 2006)
"David McVicar's production of Giulio Cesare manages to combine serious insight with entertainment, bringing Handel's masterpiece to life in a powerful, convincing and highly intelligent way. In every line of the complex narrative the subtle nuances are apparent, reflecting perfectly the transparent and exquisite nature of Handel's musical expression."--Container.
Interpr. u.a.: Sarah Connolly, Giulio Cesare. Patricia Bardon, Cornelia. Angelika Kirchschlager, Sesto. Danielle de Niese, Cleopatra. Christopher Maltman, Achilla. Christophe Dumaux, Tolomeo. Orchestra of the Age of Enlightenment. The Glyndebourne Chorus. Conductor: William Christie. - Live-Aufn.: Glyndebourne Opera House, 14 & 17 August 2005. - Ital. gesungen mit engl., franz., dt. u. span. Untertiteln
Keywords: Caesar, Julius -- Drama; Musik; Operas; Film; DVD-Video; Filmed operas; Nonfiction films; Music - Performance